2022
DOI: 10.1097/nnr.0000000000000624
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function and Self-Management Behaviors in Older Adults With Type 2 Diabetes

Abstract: Background: Type 2 diabetes (T2D) is strongly associated with cognitive impairment. Decreased cognitive function could affect daily self-management behaviors critical for people with T2D. Executive function is significant for daily self-management, and decreased subjective cognitive function could be an early indicator of poor daily self-management. However, little is known about whether executive or subjective cognitive function affects daily self-management behaviors in older adults.Objectives: We investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…An integrative review has found that cognitive dysfunction in those with T2DM can negatively impact DM-SM [ 40 ]. In clinical practice, however, cognitive health is often not part of the discussion of diabetes complications [ 41 ]. This demonstrates a need for routine screening for cognitive problems and conversations about improving or maintaining cognitive health.…”
Section: Discussionmentioning
confidence: 99%
“…An integrative review has found that cognitive dysfunction in those with T2DM can negatively impact DM-SM [ 40 ]. In clinical practice, however, cognitive health is often not part of the discussion of diabetes complications [ 41 ]. This demonstrates a need for routine screening for cognitive problems and conversations about improving or maintaining cognitive health.…”
Section: Discussionmentioning
confidence: 99%
“…El estudio de biomarcadores de etiologías específicas de la demencia como lesión del parénquima cerebral, flujo sanguíneo y metabolismo cerebrales ha tenido influencia en la investigación, así como en el diagnóstico y tratamiento de este padecimiento . Como reconocen algunos estudios (Biessels & Whitemer, 2020;Kim et al, 2023;Kim & Fritschi, 2021), es necesario llevar a cabo más investigación para determinar si las medidas de autocuidado que deben tomarse en el tratamiento de la diabetes son eficaces para evitar la aparición de deterioro cognitivo.…”
Section: Prevención Y Atención Temprana De Deterioro Cognitivo En La ...unclassified